2018
DOI: 10.1186/s12866-018-1188-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance of coagulase negative staphylococci clinical isolates from Ethiopia: a meta-analysis

Abstract: BackgroundAntimicrobial resistant Coagulase-negative Staphylococci (CoNS) have limited treatment options, rendered diseases untreatable and made hospitals to be reservoirs of the resistant strains. The aim of this study was to estimate the pooled prevalence and antimicrobial resistance of clinical isolates of CoNS from Ethiopia.ResultsThe electronic database search yielded 6511 articles of which 21 met predefined inclusion criteria. The pooled prevalence of CoNS from Ethiopia was 12% (95% confidence interval (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 51 publications
7
24
0
Order By: Relevance
“…At the mean time health workers pooreffective hygiene practices and well-functioning environmentthat can source birth canal contamination of Klebsiella to neonatal [21].likewise to this study a systematic review study done in resource limited countries had also reported that Gram-negativeorganisms,Klebsiella pneumoniae [23] was dominant isolate from child blood culture.In the other hand study from Ghanareported non-typhoidal salmonellae was dominant [24] As usual gram positive isolates shows highest level of resistance to penicillin 61.3.0% and tetracycline 78.8% which is similar with report in Jimma [8] and Gondar [16] also comparable with report of systematic review which covers most of the regions found in Ethiopia [25]. S aureus and CoNS shown high level of resistance penicillin (59%, 71.4%), Amoxicillin and Calvulanic acid (20.6%, 19%]), tetracycline (80%) andErythromycin (62% 71.4%]), which is again similar with systematic review done in Ethiopia [26].However less level of resistance was reported to Meropenem (6.4), Ceftriaxone (13%) and doxycycline (13%) that is comparable with previous study in the region [27].…”
Section: Discussionsupporting
confidence: 90%
“…At the mean time health workers pooreffective hygiene practices and well-functioning environmentthat can source birth canal contamination of Klebsiella to neonatal [21].likewise to this study a systematic review study done in resource limited countries had also reported that Gram-negativeorganisms,Klebsiella pneumoniae [23] was dominant isolate from child blood culture.In the other hand study from Ghanareported non-typhoidal salmonellae was dominant [24] As usual gram positive isolates shows highest level of resistance to penicillin 61.3.0% and tetracycline 78.8% which is similar with report in Jimma [8] and Gondar [16] also comparable with report of systematic review which covers most of the regions found in Ethiopia [25]. S aureus and CoNS shown high level of resistance penicillin (59%, 71.4%), Amoxicillin and Calvulanic acid (20.6%, 19%]), tetracycline (80%) andErythromycin (62% 71.4%]), which is again similar with systematic review done in Ethiopia [26].However less level of resistance was reported to Meropenem (6.4), Ceftriaxone (13%) and doxycycline (13%) that is comparable with previous study in the region [27].…”
Section: Discussionsupporting
confidence: 90%
“…It retains 100% of its sensitivity to commonly prescribed Beta-lactams (ampicillin, cephalexin, amoxicillin/clavulanate, penicillin G), vancomycin 83%, ciprofloxacin 86%, clindamycin 88%, erythromycin 88% and linezolid 94%. This approximates the Taiwan study and favorably exceeds the Italian one (Deyno et al, 2018;Matani et al, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…It was 100% susceptible to vancomycin and linezolid, 60~84% susceptible to cotrimoxazole, clindamycin, amoxicillin/clavulanate and cephalexin, with noticeable resistance to ciprofloxacin (47%), cloxacillin (44%), and erythromycin (33%). S. agalactiae isolated mainly in the Obstetrics and Gynecology department from vaginal swabs constitutes 25.4% of gram-positive isolates, comparable to what was found in Italy (Deyno et al, 2018), in Taiwan it was a range of 13% in non-pregnant compared to 22% in pregnant females (Matani et al, 2016). It retains 100% of its sensitivity to commonly prescribed Beta-lactams (ampicillin, cephalexin, amoxicillin/clavulanate, penicillin G), vancomycin 83%, ciprofloxacin 86%, clindamycin 88%, erythromycin 88% and linezolid 94%.…”
Section: Discussionmentioning
confidence: 62%
“…Out of isolated CONS species 74% of them were methicillin sensitive and 26% of the species were methicillin resistant. In study done by Serawit Deyno et al, [4] methicillin resistance was 37%. Different antibiotics were used to evaluate the susceptibility pattern of isolated CONS according to recommendations of CLSI 2009 guidelines for Gram Positive Bacteria [10].…”
Section: Discussionmentioning
confidence: 91%
“…These gram positive bacteria are an important cause of nosocomial infections [1]. Acquisition of genes often results in the conversion of commensal Staphylococci into invasive pathogens that causes infections especially in old, very young children and immune-compromised patients [4].…”
Section: Introductionmentioning
confidence: 99%